The Imposition of Criminal Sanctions on Perpetrators of Pedophilia in the Indonesian Legal System - Tarmina , Tarmina; Fitri Rafianti; Mhd. Azhali Siregar (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study examines the effectiveness of legal regulations in Indonesia in imposing criminal sanctions on perpetrators of pedophilia and formulates recommendations for legal reform to strengthen child protection in the future. The study uses a normative juridical approach that focuses on the study of written legal norms, particularly provisions in the Criminal Code (KUHP), Law Number 23 of 2002 concerning Child Protection as amended by Law Number 35 of 2014, and Law Number 17 of 2016 which introduced additional penalties in the form of chemical castration. The results of the study indicate that normatively the existing regulations are quite progressive, as seen from the increase in the minimum criminal penalty of five years and a maximum of fifteen years, increased sentences for perpetrators who have a special relationship with children, the introduction of restitution for victims, and additional special penalties. However, the effectiveness of these regulations still faces several obstacles, including a weak understanding of the characteristics of pedophilia among law enforcement officials, disparities in sentencing, limited restitution mechanisms, and minimal psychological protection for child victims in the judicial process. This study recommends several legal reform measures, including codifying specific laws regarding child protection, strengthening the explicit definition of pedophilia in the law, classifying criminal offenses based on severity, automated mechanisms for granting restitution, utilizing technology to protect victims in court, and strengthening rehabilitation programs for perpetrators with mental disorders. Furthermore, harmonizing national regulations with international instruments such as the Convention on the Rights of the Child is also crucial to ensure child protection standards align with global commitments. By implementing these reforms, it is hoped that the Indonesian legal system will not only serve to punish perpetrators but will also be able to deliver substantive justice by guaranteeing the recovery, protection, and best interests of children as victims of pedophilia